Double-edged swords: Expert-stakeholders as (slightly) unreliable instruments for control and autonomy of executive agencies - Schillemans, Thomas (2012)
Establishing executive agencies at arms's length of parent departments has caused widespread concern regarding their autonomy. In the Netherlands, ministries have established different types of boards to monitor agencies. Also, agencies have established an independent review commission. The different boards and the review commission can be looked at as expert stakeholders. This article poses the question whether and how expert stakeholders contribute to either the ministries' control on agencies or the autonomy of agencies. The article is based on qualitative research on six of the largest executive agencies. The article concludes that expert stakeholders act as double-edged swords: they contribute to control on agencies but also to their autonomy. Expert stakeholders improve the monitoring capacity of ministries and thus contribute to control. Conversely, they also strengthen agencies, as they provide political multiplicity and boost reputational uniqueness. The question of which of these prevails is mainly influenced by time, capture, and policy crises. - Reproduced.
Keywords: Public administration